Uniform nonsquareness of direct sums of Banach spaces - Betiuk-Pilarska, Anna; Prus, Stanisław (Topological Methods in Nonlinear Analysis, 2009)
An inequality between James constants of Banach spaces X_s and the James constant of their direct sum is obtained. This gives a characterization of uniform nonsquareness of sums of Banach spaces.